PENERAPAN PRINSIP MODIFIKASI PERILAKU UNTUK MENINGKATKAN KEMAMPUAN MENYIKAT GIGI PADA ANAK DENGAN DISABILITAS INTELEKTUAL BERAT - Hapsari, Catherina Kartika; Hartiani, Fenny (Jurnal Psikologi, 2018)
Self-help skills are one of the skills needed to support one's life. Individuals with severe intellectual disability have difficulty to perform self-help tasks, such as dressing, bathing, and toothbrushing. In addition, individuals with intellectual disability usually have other health related problems. To prevent dental health problems among people with severe intellectual disability, it is necessary to prevent it by taking care of dental health. Toothbrushing is one of the most effective ways to prevent it and toothbrushing training are one of intervention that could help. This research applied behaviour modification total-task presentation in children with severe intellectual disability. This research is a quasi-experimental research using a single subject A-B-A design. The participants for this study were a 19-year-old female teenager with severe intellectual disability. This intervention was given as many as nine sessions in three weeks. The data were collected using interviews and observations to record the emergence of a series toothbrushing behavior. Data then analysed using visual inspections method. The results of this study indicate that the total task presentation intervention provides an improvement in the ability of brushing teeth. This improvement still needs to be supported by the carer's directions.